Colonic Diaphragm Disease in a Patient Receiving Long Term Diclofenac Therapy - Alan A Weiss; David A Owen (Canadian Journal of Gastroenterology)
A 65-year-old woman who had been taking diclofenac for five years developed cramping central abdominal pain. Barium enema examination was negative, but colonoscopy revealed prominent mucosal folds in the right colon with areas of ulceration. Because of continued symptoms, a right hemicolectomy was performed, which showed four separate short segment strictures or diaphragms. This case demonstrates a rare complication of nonsteroidal anti-inflammatory agent therapy that should be considered in the differential diagnosis of unexplained abdominal pain.